1998
DOI: 10.1093/oxfordjournals.alcalc.a008346
|View full text |Cite
|
Sign up to set email alerts
|

Violence and Alcoholism in the Family: How Are the Children Affected?

Abstract: -We made an evaluation of how children and adolescents are affected if they live in a family environment where violence associated with alcoholism is a feature. Interviews with 20 f«mili« and the use of psychological tests on their children were perfonned in this study. The study has demonstrated the existence of psychopathological disturbances in those families' children, whose immaturity and insecurity were expressed by aggressive behaviour or by depressive manifestations. It also became evident that there w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…Cleaver et al, 1999Cleaver et al, , 2007Evans, 2006;Fergusson and Horwood, 1998;Galvani, 2004Galvani, , 2006Galvani, , 2007aGalvani, , 2007bGorin, 2004;Hester et al, 2000;Irons and Schneider, 1997;Kemmner et al, 2004;Kindler, 2002;Mullender et al, 2002;Templeton et al, 2006;Velleman and Orford, 1999). What seems to be clear is that if children live with both problems, they are at an even higher risk of a range of negative outcomes, in all areas of health, safety, emotional and social and development (Cleaver et al, 2007;Galvani, 2006;Malpique et al, 1998;Ritter et al, 2002). If other factors are also present (both parents misusing alcohol, housing problems, unemployment, parental mental health problems, etc.…”
Section: Strainmentioning
confidence: 99%
“…Cleaver et al, 1999Cleaver et al, , 2007Evans, 2006;Fergusson and Horwood, 1998;Galvani, 2004Galvani, , 2006Galvani, , 2007aGalvani, , 2007bGorin, 2004;Hester et al, 2000;Irons and Schneider, 1997;Kemmner et al, 2004;Kindler, 2002;Mullender et al, 2002;Templeton et al, 2006;Velleman and Orford, 1999). What seems to be clear is that if children live with both problems, they are at an even higher risk of a range of negative outcomes, in all areas of health, safety, emotional and social and development (Cleaver et al, 2007;Galvani, 2006;Malpique et al, 1998;Ritter et al, 2002). If other factors are also present (both parents misusing alcohol, housing problems, unemployment, parental mental health problems, etc.…”
Section: Strainmentioning
confidence: 99%
“…Alcohol addiction severely compromises or destroys the ability of parents to provide a safe and nurturing home for a child (CASA, 1999a). COAs often grow up in chaotic, confused, and unstable environments, characterized by poor family management, conflict, role confusion, instability, lack of supervision, little emotional support, and social isolation (Austin & Prendergast, 1991; Jester et al, 2000; Kumpfer & DeMarsh, 1986; Malpique et al, 1998; Williams, 1996). In their study of inner-city African-American female caregivers, Jester and colleagues (2000) found that families with caregivers who were frequent heavy drinkers were more than three times as likely as those with lighter-drinking caregivers to be at risk for poor family functioning, more than twice as likely to provide their children with low intellectual stimulation, and nearly three times as likely to have high levels of domestic violence.…”
Section: Parental Use Of Alcohol or Tobacco And Children’s Healthmentioning
confidence: 99%
“…COAs are often under immense psychological stress (Austin & Prendergast, 1991; Johnson & Leff, 1999; Kumpfer & DeMarsh, 1986; Sher, 1991). The behavior of alcohol abusers is often inconsistent and unpredictable, making it very difficult for children to feel relaxed or calm in their presence (Barnard, 1999; Malpique et al, 1998; Velleman & Orford, 1990). These children often live in constant fear of physical or emotional abuse…”
Section: Parental Use Of Alcohol or Tobacco And Children’s Healthmentioning
confidence: 99%
“…Este test temático se utiliza también en investigación (Jiménez, López, Pereda, González & Gómez, 1986;Bachs, 1990;Yárnoz, 1993;Malpique, 1998;Boekholt, 2000;Schwart & Caride, 2001;Ballús, 2010;Ballús, Bachs & Pérez, 2010;Brando, Valera & Zarate, 2008). Sin embargo, tal y como ya han señalado algunos autores (Exner, 1976;Singer, 1968), la utilización de técnicas proyectivas tiene el inconveniente de que algunas de ellas no aportan la suficiente fiabilidad y validez en los procedimientos de corrección e interpretación como para poder categorizar la gran cantidad de datos cualitativos que se obtienen.…”
Section: Introductionunclassified